2013
DOI: 10.1038/onc.2013.312
|View full text |Cite
|
Sign up to set email alerts
|

Early epigenetic downregulation of WNK2 kinase during pancreatic ductal adenocarcinoma development

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is usually incurable. Contrary to genetic mechanisms involved in PDAC pathogenesis, epigenetic alterations are ill defined. Here, we determine the contribution of epigenetically silenced genes to the development of PDAC. We analyzed enriched, highly methylated DNAs from PDACs, chronic pancreatitis (CP) and normal tissues using CpG island microarrays and identified WNK2 as a prominent candidate tumor suppressor gene being downregulated early in PDAC development. WNK2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…WNK kinases play an important role in cell cycle progression, metabolic adaptation, antiapoptosis, invasion, and metastasis. 29 Epigenetic silencing of WNK2 has been found in gliomas, meningiomas, and pancreatic ductal adenocarcinomas; [30][31][32] however, the functional impact of genetic mechanisms affecting WNK2 is still unknown, especially in cancer. 29 We showed that in addition to somatic mutations in WNK2, copy number loss occurred in nearly 30% of patients, and WNK2 expression in the tumor samples was also downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…WNK kinases play an important role in cell cycle progression, metabolic adaptation, antiapoptosis, invasion, and metastasis. 29 Epigenetic silencing of WNK2 has been found in gliomas, meningiomas, and pancreatic ductal adenocarcinomas; [30][31][32] however, the functional impact of genetic mechanisms affecting WNK2 is still unknown, especially in cancer. 29 We showed that in addition to somatic mutations in WNK2, copy number loss occurred in nearly 30% of patients, and WNK2 expression in the tumor samples was also downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…The total RNA was reverse-transcribed using Omniscript reverse transcriptase (Qiagen, Hilden, Germany). Sequences of RT-PCR primers employed were as follows: mouse C/EBPβ sense, 5′-GTTTCGGGAGTTGATGCAATC-3′, C/EBPβ antisense, 5′-AACAACCCCGCAGGAACAT-3′; mouse CUL3 sense, 5′-GGATGAGTTCAGGCAACATC-3′, mouse CUL3 antisense, 5′-GCATGTCTTGGTGCTGGTGG-3′; human perilipin sense, 5′- ACCCCCCTGAAAAGATTGCTT-3′, antisense, 5′- GATGGGAACGCTGATGCTGTT-3′; human PPARγ2 sense, 5′-GCAGGAGATCTACAAGGACTTG-3′, antisense, 5′- CCCTCAGAATAGTGCAACTGG-3′; human β-actin sense, 5′-CCGTCTTCCCCTCCATCG-3′; antisense, 5′- GTCCCAGTTGGTGACGATGC-3′; the mouse C/EBPα, mouse PPARγ, mouse β-actin, mouse GAPDH, mouse FAS, mouse LPL, mouse FABP4, mouse WNK2, mouse WNK3, mouse WNK4, mouse KLHL2, mouse KLHL3, mouse F4/80, and mouse adiponectin primers were described previously (Zeniya et al, 2013, Madsen et al, 2003, O'reilly et al, 2006, Dutruel et al, 2014, Suganami et al, 2005). Relative mRNA levels were normalized by endogenous reference genes (β-actin and GAPDH).…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly significantly considering that cytoplasmic pERK has been detected in a large number of patient PDAC samples (Pham et al. , 2008; Dutruel et al. , 2014).…”
Section: Discussionmentioning
confidence: 99%